PERBANDINGAN CAPAIAN PEMBELAJARAN MODEL COOPERATIVE LEARNING DAN MODEL PEMBELAJARAN CERAMAH DI SMK PANGUDI LUHUR RAHAYU II CIJANTUNG - Gaudensius Dennys; Tarsicius Sunaryo (Jurnal Manajemen Pendidikan, 2018)
Improving the quality of education and development of learning process is a problem that always demands attention. Differences between students absorb the level of the other students to learning materials demands a teacher to make innovations in learning so that not only presents the material, but also need to use appropriate methods, liked,and students easy to understand. Especially in art learning, teacher innovation in teaching is very necessary for improving student learning outcomes. In this research, the researcher compared two methods of learning Cooperative Learning and Lecture as a compare in the learning process of music art. To study it, this research can do with the formulation of the problem such as: How is the comparison of students learning achievement between lessons cooperative learning model and lecture? The result of the research shows that: (1) Using the Cooperative Learning method can improve students learning outcomes compared to Lecture method on vocal test, ensemble and skill, (2) there is significant influence between Cooperative Learning method and students learning outcomes with sig t 0,000 < 0, 05 it means there is a significant relationship. Based on the results of research can give suggestions such as : (1) The teachers can use cooperative learning method to improve the willingness of students and learning outcomes in follow the lessons, (2) need to do further research to determine the other influence of learning models to improve learning outcomes and students interest to learn.